Weed community ecology : Tedious sampling or relevant science? A Canadian perspective - Derksen, D.A. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
The study of weed community ecology involves aspects of species life forms, diversity, and spatial and temporal variability. Previously, Canadian research in this area focused on weed surveys, while recent research has been conducted on community composition as influenced by tillage System and crop rotation. New techniques in multivariate ordination have been used to analyse weeds at a community rather than a species level, with a resultant new understanding of community dynamics. Although the study of weed community ecology often involves tedious sampling, increased research in this area would provide the basis for the development of effective integrated weed management strategies. This paper discusses aspects of weed community ecology in light of Canadian research and makes recommendations for future studies.